2017
DOI: 10.1111/cmi.12709
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-99 family modulates hepatitis B virus replication by promoting IGF-1R/PI3K/Akt/mTOR/ULK1 signaling-induced autophagy

Abstract: MicroRNAs are small highly conserved noncoding RNAs that are widely expressed in multicellular organisms and participate in the regulation of various cellular processes including autophagy and viral replication. Evidently, microRNAs are able to modulate host gene expression and thereby inhibit or enhance hepatitis B virus (HBV) replication. The miR-99 family members are highly expressed in the liver. Interestingly, the plasma levels of miR-99 family in the peripheral blood correspond with HBV DNA loads. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 73 publications
6
108
0
Order By: Relevance
“…Previous studies in HBV transgenic mice have illustrated, for example, that fasting decreases glucose levels but increases HBeAg synthesis in serum. However, autophagy significantly promotes HBsAg and virion production but not HBeAg production, as shown in several early studies (Lin et al, 2017;Lin, Wu, Wang, Kemper, et al, 2019;Lin, Wu, Wang, Liu, et al, 2019). In this study, the expression of transcription factors, including PGC1α, CREB, and ChREBP, was found to be altered by these indicated glucose concentrations in the cell cultures and correlated with changes in the HBV RNAs levels.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Previous studies in HBV transgenic mice have illustrated, for example, that fasting decreases glucose levels but increases HBeAg synthesis in serum. However, autophagy significantly promotes HBsAg and virion production but not HBeAg production, as shown in several early studies (Lin et al, 2017;Lin, Wu, Wang, Kemper, et al, 2019;Lin, Wu, Wang, Liu, et al, 2019). In this study, the expression of transcription factors, including PGC1α, CREB, and ChREBP, was found to be altered by these indicated glucose concentrations in the cell cultures and correlated with changes in the HBV RNAs levels.…”
Section: Discussionsupporting
confidence: 72%
“…Maintaining energy homeostasis is very important in mammalian physiology. Previously, we tested several mTOR-related pathways and found that SREBP1 was also partly activated to regulate HBV replication (Lin et al, 2017). Herein, HBV replication decreased after 2-DG treatment in HepG2.2.15 cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The PI3K/Akt signaling pathway regulates the crucial cellular biological process involved in the genesis and development of cancer, including transcription, translation, metabolism, angiogenesis, apoptosis, proliferation, and regulation of cell cycle progression, migration and invasion of cells (26,27). p-Akt is able to phosphorylate the downstream tyrosine and tryptophan residues, so as to activate downstream factors, cause the apoptosis of suppressor cells, promote cellular proliferation, growth, movement and invasion, and promote tumor angiogenesis (28). In vivo and in vitro experiments have indicated that following restrained activity of the PI3K-Akt signaling pathway, pancreatic cancer cells undergo hindered proliferation, promoted apoptosis and reduced invasive ability (29).…”
Section: Discussionmentioning
confidence: 99%